Geological context of the Boumnyebel talcschists (Cameroun): Inferences on the Pan-African Belt of Central Africa Le contexte géologique des talcschistes de Boumnyebel (Cameroun) : implications pour la chaîne panafricaine d'Afrique centrale - (:unkn) unknown (My University, 2010)
The talcschists of the Boumnyebel area (southern Cameroon) form ≤ 30 m thick discontinuous layers within a Pan-African nappe unit (Yaoundé group), which includes, at the base, muscovite + biotite ± garnet micaschists associated with amphibolites and pyroxenites, and, at the top, muscovite + biotite + garnet + kyanite micaschists locally associated with marble and amphibolites. The metamorphic peak (not, vert, similar650 °C/9.5 kbar; ca. 620 Ma) postdates nappe emplacement. Isograds are in normal position, micaschists passing downwards to migmatites in the northwestern part of the area studied. The rock types in the lower part of this nappe suggest active margin environments with detrital input from a nearby continental crust (arc or back-arc context).
Keywords: African Research